SOSIALISASI PERILAKU ECO-DRIVING BAGI PENGENDARA SEPEDA MOTOR USIA REMAJA MENUJU PENGHEMATAN ENERGI FOSIL - Kemas, Abdul Fattah; Indriyani (MAJU : Indonesian Journal of Community Empowerment, 2024)
Along with the growth of the vehicle population, there is an increase in fuel consumption, where fuel is a source of fossil energy, so at some point, this fossil energy source will run out. For this reason, saving efforts are needed. The growth in the motorized vehicle population is also accompanied by an increase in school-aged or teenage motorcyclists, so efforts to save fuel consumption should also involve school-aged or teenage riders. Eco-driving behaviour needs to be socialized to them. This PKM activity aims to provide knowledge to school-aged or teenage motorbike riders so that there is a willingness to cultivate eco-driving behaviour. Based on the analysis carried out using the paired t-test, the knowledge of socialization participants increased significantly. With this increase in knowledge, it is expected that eco-driving behaviour can become a driving culture, especially for school-aged or teenage drivers.